2016
DOI: 10.1007/s13187-016-1067-5
|View full text |Cite
|
Sign up to set email alerts
|

Views on clinical trial recruitment, biospecimen collection, and cancer research: population science from landscapes of the Haudenosaunee (People of the Longhouse)

Abstract: Biomedical research in culturally distinct communities is often a challenge. Potential barriers to participation occur because science is presented in a format that lacks cultural acknowledgement. Investigations may also fail to showcase beneficial relevance to the communities or include them in true partnership. The history of biomedical research within Native American societies has been complicated by these issues. Historical trauma among many Native groups sometimes transcends into contemporary challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…We recognize this is often difficult for clinical researchers for a number of reasons: geographic and infrastructure impediments to equitable dissemination of clinical trials to underserved communities; referral patterns by providers who may not be adequately informed about availability of trials; and that many racial/ethnic minorities are distrusting of unique and experimental therapies (Schmotzer, 2012). In addition, some underserved and racial/ethnic populations face challenges with completing trials because of factors such as financial burden, lack of transportation and family responsibilities (Brown et al, 2000; Ford et al, 2008; Haring et al, 2016; Schmotzer, 2012; Sprague et al, 2013). Still, researchers must commit to making a deliberate change to including patients from diverse backgrounds to comprehensively understand their experiences of disease and treatment.…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…We recognize this is often difficult for clinical researchers for a number of reasons: geographic and infrastructure impediments to equitable dissemination of clinical trials to underserved communities; referral patterns by providers who may not be adequately informed about availability of trials; and that many racial/ethnic minorities are distrusting of unique and experimental therapies (Schmotzer, 2012). In addition, some underserved and racial/ethnic populations face challenges with completing trials because of factors such as financial burden, lack of transportation and family responsibilities (Brown et al, 2000; Ford et al, 2008; Haring et al, 2016; Schmotzer, 2012; Sprague et al, 2013). Still, researchers must commit to making a deliberate change to including patients from diverse backgrounds to comprehensively understand their experiences of disease and treatment.…”
Section: The Connect Frameworkmentioning
confidence: 99%
“…The paucity of diversity in biospecimen science and cancer genomic studies are potentially more tied to a lack of communication and engagement of diverse and underserved populations as opposed to their willingness/unwillingness to participate and/or reasons related to medical distrust . Formative research efforts that are inclusive of diverse and underserved populations regarding biospecimen science have shed some light on the following areas: awareness and interest in biospecimen donation for research, reasons for nonparticipation, collaborative study designs that include community‐based approaches to engage and integrate community research partners, and underserved populations in this type of research, in addition to data regarding cultural perspectives and requirements for research specific to biospecimen science . In fact, exploratory studies examining motivational factors and barriers to participation in biospecimen donation from diverse racial and ethnic minorities have suggested that the majority of African Americans and Hispanics/Latinos are willing to donate different types of biospecimens and that they do donate when asked …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Formative research efforts that are inclusive of diverse and underserved populations regarding biospecimen science have shed some light on the following areas: awareness and interest in biospecimen donation for research, reasons for nonparticipation, collaborative study designs that include community-based approaches to engage and integrate community research partners, and underserved populations in this type of research, in addition to data regarding cultural perspectives and requirements for research specific to biospecimen science. [14][15][16][17][18] In fact, exploratory studies examining motivational factors and barriers to participation in biospecimen donation from diverse racial and ethnic minorities have suggested that the majority of African Americans and Hispanics/ Latinos are willing to donate different types of biospecimens and that they do donate when asked. 19 The purpose of the current study was to examine factors associated with opportunity, actual participation, and willingness to participate in biomedical research broadly and specifically related to clinical trials and biospecimen donation among a diverse, multilingual sample across 3 distinct geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…We were of the opinion that, even though some members of the Māori community were opposed to genetic research, there were many instances where families were given no choice about participation with genetic research (Guilford et al 1998;Guilford et al 2010) or were choosing to participate to address health issues (Port et al 2008). We have specifically added the cultural dimension to the ELSI acronym to reflect the unique cultural worldviews that Indigenous communities bring to ELSI-or better, CELSI-debates (Arbour and Cook 2006;Garrison 2013;Haring et al 2018;Hiratsuka, Brown, and Dillard 2012;TallBear 2013;Taualii et al 2014).…”
Section: References Citedmentioning
confidence: 99%